Experimental and Theoretical Study of Combustion under Elevated Pressure within Porous Inert Media. Issue 7 (11th May 2017) - Bedoya, Cesar; Zarzalis, Nikolaos; Habisreuther, Peter
Abstract: Gas combustion occurring within porous inert media (PIM) results in intensified heat and mass transfer in comparison to free laminar combustion. This leads to considerably lower emissions of pollutant species, that is, NO x and CO, larger flame stability range, lower thermo‐acoustic instabilities, gradual response to operative changes, and geometric flexibility of design. In this work, experiments were carried out to describe the influence of flow rate, pressure, temperature, and air‐to‐fuel ratio on the flame stability within PIM at nearly adiabatic conditions. The macroscopic thermal flame thickness and the burning velocity were calculated from measured temperature profiles and flow rates. As the main result, it was observed that the pressure effect on the burning velocity can differ considerably from that of laminar free flames, that is, the increase of pressure can positively affect the burning velocity. The obtained results were supported by theoretical modeling. A new model to average the species production rates in a volume‐averaged numerical model was proposed. The model considered spatial deviations of temperature and mass fractions along the cross‐sectional area using presumed probability density functions. Using this new model, results of burning velocities and profiles of average temperature were satisfactorily predicted when compared to experimental results shown here. Furthermore, easy‐to‐use tools for porous burner design were formulated and validated. Abstract : Flaming pores : A comprehensive study of stationary flames within porous inert media (PIM) is performed at elevated pressure. Here, it is shown that: 1) the effect of pressure on the burning velocity in PIM differs to that in laminar free flames; the reason can be attributed to dispersion. 2) The flame structure in PIM is corrugated. 3) The (wide) macroscopic flame thickness can only be accurately predicted if spatial temperature deviations are considered.